Changes in SME business due to COVID-19: Survey in Slovakia and the Czech Republic - Andrea Janáková Sujová; Václav Kupčák (Economies, 2023)
The objective of the paper is to analyse and compare the consequences of the coronacrisis on the entrepreneurship of small and medium-sized enterprises (SMEs) in Slovakia and the Czech Republic with the aim of identifying the determinants of changes in entrepreneurship. The secondary empirical research was carried out based on the analysis of secondary and primary data. The analysis used economic indicators of SMEs, governmental measures and surveys of the views of entrepreneurs. The analysis used data from statistical databases and official reports from government institutions and non-governmental organisations (NGOs), as well as data from primary surveys conducted by NGOs. Descriptive statistics, financial analysis and cross-comparison methods were used to process the data. The results revealed changes in the business of SMEs in the Czech Republic and Slovakia during the crisis, such as the adaptation of business strategies, improvement of flexibility and acceleration of digitalisation processes. These changes highlighted the importance of building business agility. The summary of the main changes in SME business based on both secondary data and primary surveys and the perception of state anti-pandemic aid by managers as feedback to governments represent the main contributions of the paper.
Keywords: 330; coronacrisis; small and medium-sized enterprises; anti-pandemic measures; state aid; enterprise agility